Anthropogenic impacts on Keshalia River, Eastern Nepal - Shrestha, Jay Narayan (Nepalese Journal of Biosciences, 2017)
The anthropogenic impact on Keshalia river, especially on fish diversity, is very high. Over fishing with unconventional fishing methods, disposal of domestic and industrial effluents, excess use of pesticides, dumping sites of municipalities, dam construction without fish ladder across the river and mining of sands and gravels are major anthropogenic impacts on the river.